2015
DOI: 10.1016/j.euroecorev.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fiscal inflation

Abstract: Fiscal theorists warn about the risk of future in ‡ation as a consequence of current …scal imbalances in the US. Because actual in ‡ation remains historically low and data on in ‡ation expectations do not corroborate such risks, warnings for …scal in ‡ation are often ignored in policy and academic circles. This paper shows that a canonical NK-DSGE model enables identifying an anticipated component of in ‡ation expectations that is closely related to …scal policy. Estimation results suggest that …scal in ‡ation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Sergey Pekarski [17] examined shifts in moderate and hyperinflation occurring because of shifts in monetary and fiscal policy by considering Laffer curve-represents the relationship between the tax rate and the amount of tax collected by governments, which is used to illustrate the Laffer's argument that sometimes cutting tax rate can increase total revenue [25], and Olivera-Tanzi effect-an economic situation involving a period of high inflation and a decline in tax revenues, which can divide the budget deficit effect into two parts, one part, which is subject to negative inflation, and the second part, which is inflation proof. Graeve and Heideken [18] discussed anticipated inflation, which is strictly related to fiscal policy, and pointed out that warnings for fiscal inflation are always ignored in policies. The results suggested that fiscal inflation had already induced a 1.6 percent points increase in long-term inflation in 2001.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sergey Pekarski [17] examined shifts in moderate and hyperinflation occurring because of shifts in monetary and fiscal policy by considering Laffer curve-represents the relationship between the tax rate and the amount of tax collected by governments, which is used to illustrate the Laffer's argument that sometimes cutting tax rate can increase total revenue [25], and Olivera-Tanzi effect-an economic situation involving a period of high inflation and a decline in tax revenues, which can divide the budget deficit effect into two parts, one part, which is subject to negative inflation, and the second part, which is inflation proof. Graeve and Heideken [18] discussed anticipated inflation, which is strictly related to fiscal policy, and pointed out that warnings for fiscal inflation are always ignored in policies. The results suggested that fiscal inflation had already induced a 1.6 percent points increase in long-term inflation in 2001.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the Monetarist school of thought argued that budget deficit affects money supply and inflation through financing methods. A plethora of studies has been done on the relationships of fiscal deficit and inflation [15][16][17][18][19].However, these studies have only analyzed the fiscal deficit and inflation as theoretically described in the fiscal theory of price, but another side of the fence has been ignored, which is the sources to finance the fiscal deficit and its inflation cost. It is essential to address the budget balance because, in the short run, it becomes crucial for the government to control inflation in the country [20].…”
Section: Introductionmentioning
confidence: 99%